Development and evaluation of a human machine interface to support mode awareness in different automated driving modes. (January 2023) - Tinga, Angelica M.; van Zeumeren, Ilse M.; Christoph, Michiel; van Grondelle, Elmer; Cleij, Diane; Aldea, Anna; van Nes, Nicole
Highlights: An HMI creating mode awareness during automated driving is developed and evaluated. Functional requirements, based on literature and 5 experiments, were implemented. Next steps were set using VR and RITE (Rapid Iterative Testing and Evaluation) The final continuous and holistic design creates mode awareness through ambience. Findings show that the final design was comprehended well and had a good usability. Abstract: With increasing implementation of automated driving technology it is expected that different automation modes will be present within the same vehicle and within a single trip. At all times during automated driving the driver needs to have 'mode awareness', which is an understanding of the automation mode and the corresponding responsibilities. Yet, research on HMI design to support mode awareness for multiple automation modes within a single vehicle and within a single trip is currently limited. The current work describes the development and evaluation of a Human Machine Interface (HMI) to support mode awareness while driving in different automation modes. The work exists of three phases: Phase 1 defines functional requirements for HMI design based on literature review and 5 experimental studies including 146 participants. Phase 2 implements the functional requirements in HMI design through expert and focus group sessions. Phase 3 evaluates and improves upon the HMI design employing virtual reality and the RITE (Rapid Iterative Testing and Evaluation) method with 18 participants. The result is a continuous and holistic HMI design creating mode awareness through ambience. Findings from Phase 3 and previous research indicate that this HMI is comprehended well, with a relatively low task load, and with a good experienced system usability. It is important to additionally evaluate the HMI design resulting from the current study in driving simulators and in on-road tests. Such tests will provide an opportunity to verify and expand on the current study's findings and to contribute to guidelines for HMI design.